Proteomic profiling of human bone from different anatomical sites – A pilot study. Issue 5 (3rd May 2022) - Fretwurst, Tobias; Tritschler, Isabel; Rothweiler, René; Nahles, Susanne; Altmann, Brigitte; Schilling, Oliver; Nelson, Katja
Abstract: Purpose: The study aim is a comparative proteome‐based analysis of different autologous bone entities (alveolar bone [AB], iliac cortical [IC] bone, and iliac spongiosa [IS]) used for alveolar onlay grafting. Experimental Design: Site‐matched bone samples of AB, IC, and IS were harvested during alveolar onlay grafting. Proteins were extracted using a detergent‐based (sodium dodecyl sulfate) strategy and trypsinized. Proteome analysis was performed using liquid chromatography–tandem mass spectrometry (LC‐MS/MS). MaxQuant was used for peptide‐to‐spectrum matching, peak detection, and quantitation. Linear models for microarray analysis (LIMMA) were used to detect differentially abundant peptides and proteins. Results: A total of 1730 different proteins were identified across the 15 samples at a false discovery rate of 1%. Partial least‐squares discriminant analysis approved segregation of AB, IC, and IS protein profiles. LIMMA statistics highlighted 66 proteins that were more abundant in AB then in IC (vs. 92 proteins were enriched in IC over AB). Gene Ontology enrichment analysis revealed a matrisomal versus an immune‐related proteome fingerprint in AB versus IC. Conclusion and Clinical Relevance: This pilot study demonstrates an ECM protein‐related proteome fingerprint in AB and an immune‐related proteome fingerprint in IS and IC.